Selective Ablation and Laser-Induced Periodical Surface Structures (LIPSS) Produced on (Ni/Ti) Nano Layer Thin Film with Ultra-Short Laser Pulses - Biljana Gaković; Suzana Petrović; Christina Siogka; Dubravka Milovanović; Miloš Momčilović; George D. Tsibidis; Emmanuel Stratakis (Photonics)
The interaction of ultra-short laser pulses (USLP) with Nickel/Titanium (Ni/Ti) thin film has been presented. The nano layer thin film (NLTF), composed of ten alternating Ni and Ti layers, was deposited on silicon (Si) substrate by ion-sputtering. A single and multi-pulse irradiation was performed in air with focused and linearly polarized laser pulses. For achieving selective ablation of one or more surface layers, without reaching the Si substrate, single pulse energy was gradually increased from near the ablation threshold value to an energy value that caused the complete removal of the NLTF. In addition to single-pulse selective ablation, the multi-pulse USLP irradiation and production of laser-induced periodic surface structures (LIPSSs) were also studied. In the presented experiment, we found the optimal combination of accumulated pulse number and pulse energy to achieve the LIPSS formation on the thin film. The laser-induced morphology was examined with optical microscopy, scanning electron microscopy, and optical profilometry. To interpret the experimental observations, a theoretical simulation has been performed to explore the thermal response of the NLTFs after irradiation with single laser pulses.